2020
DOI: 10.3389/fnhum.2020.00300
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Glymphatic System Using Diffusion MR Technique in T2DM Cases

Abstract: Objective: We aimed to evaluate the activity of the human glymphatic system in type 2 diabetes mellitus (T2DM) using diffusion tensor image analysis along with the perivascular space (DTI-ALPS). Methods: Diffusion tensor images were acquired to calculate the diffusivities in the direction of the x-axis (right-to-left; Dx), y-axis (anterior-to-posterior; Dy), and z-axis (inferior-to-superior; Dz) of the plane of the lateral ventricle body in 20 patients with type 2 diabetes and 10 people in a control group. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 28 publications
2
63
2
Order By: Relevance
“…This was possibly due to the low number of diabetic subjects, and that most subjects had relatively good sleep conditions. While a recent study ( Yang et al, 2020 ) suggests that patients with type 2 diabetes mellitus had reduced ALPS, their sample size was also very small. Future studies should investigate the influence of these factors in more dedicated large samples.…”
Section: Discussionmentioning
confidence: 93%
“…This was possibly due to the low number of diabetic subjects, and that most subjects had relatively good sleep conditions. While a recent study ( Yang et al, 2020 ) suggests that patients with type 2 diabetes mellitus had reduced ALPS, their sample size was also very small. Future studies should investigate the influence of these factors in more dedicated large samples.…”
Section: Discussionmentioning
confidence: 93%
“…The DTI-ALPS method is used for evaluating the glymphatic system's function or the interstitial fluid dynamics, and this method has been adopted in several studies evaluating the alteration of the glymphatic system or interstitial fluid dynamics in various pathologies [21][22][23][24][25][26][27][28]. One of the report showed that results of ALPS method were significantly related to glymphatic clearance function calculated on MRI by intrathecal administration of GBCA [28].…”
Section: Discussionmentioning
confidence: 99%
“…The DTI-ALPS method provides ALPS index, which is a ratio of the diffusivity in the direction of the perivascular space and the diffusivity in the direction perpendicular to both major fiber tract and perivascular space, based on a special spatial relationship in the fiber tracts and the perivascular space in the axial imaging plane at the corona radiata [19,20]. Recently, the DTI-ALPS method has been adopted in several studies evaluating the alteration of the glymphatic system or interstitial fluid dynamics in various pathologies [21][22][23][24][25][26][27][28]. These reports indicated that the ALPS-index is a useful biomarker to evaluate the interstitial fluid dynamics or glymphatic function.…”
Section: Introductionmentioning
confidence: 99%
“…Although this method is based on a deductive model, it is frequently used to investigate human glymphatic function. Its potential to serve as an imaging marker of glymphatic activity has been reported in many clinical conditions such as Alzheimer’s disease ( 10 , 30 ), normal pressure hydrocephalus ( 31 , 32 ), Parkinson disease ( 33 , 34 ), age-related iron deposition ( 15 ), diabetic cognitive impairment ( 35 ), and meningioma-associated brain edema ( 17 ). However, there are limitations to this method and, consequently, our study.…”
Section: Discussionmentioning
confidence: 99%